2003
DOI: 10.1002/eat.10197
|View full text |Cite
|
Sign up to set email alerts
|

Self‐competence and self‐liking in the prediction of change in bulimic symptoms

Abstract: These findings have significant theoretic implications for the construct of self-esteem and implications for risk for and treatment of bulimia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…Results from this sample have been previously reported. 11,27,28 Procedure At time 1 (T1) and time 2 (T2), spaced 11 weeks apart, participants completed questionnaires related to person-ality and disordered eating. Between T1 and T2, participants completed inventories weekly on assigned dates for 10 weeks, reporting on their previous week's weight/ shape, interpersonal, and academic stressors.…”
Section: Participantsmentioning
confidence: 99%
“…Results from this sample have been previously reported. 11,27,28 Procedure At time 1 (T1) and time 2 (T2), spaced 11 weeks apart, participants completed questionnaires related to person-ality and disordered eating. Between T1 and T2, participants completed inventories weekly on assigned dates for 10 weeks, reporting on their previous week's weight/ shape, interpersonal, and academic stressors.…”
Section: Participantsmentioning
confidence: 99%
“…Many empirical studies employing a two-dimensional model of self-esteem have focused on university students (for example, Tafarodi and Milne 2002;Tafarodi and Swann 2001) and other groups of adults, such as patients suffering from eating disorders (Surgenor et al 2006;Sassaroli and Ruggiero 2005;Bardone et al 2003). It is only recently that such measures have been employed in studies in primary classrooms (see Miller and Lavin 2007;Miller and Moran 2007), helping to illuminate aspects of classroom practice and children's perceptions.…”
Section: Implications For Further Researchmentioning
confidence: 99%
“…Though a strong relationship between self-liking and the presence of eating disorder symptoms was found, no significant associations with selfcompetence was noted. In a sample of people with bulimia nervosa (BN), Bardone, Perez, Abramson, & Joiner (2003) found that while both self-liking and self-competence were related to symptoms in a cross-sectional design, self-competence alone predicted change in symptomatology over time.…”
Section: Introductionmentioning
confidence: 98%